Impacts of Land Use Change on Urban Heat Islands in Kribi, Cameroon: Assessing Vulnerability and Adaptive Strategies - Fendoung, Philippes Mbevo; Moto, Fabrice Armel Mvogo; Makuate, Marie Brigitte (European Scientific Journal, ESJ, 2024)
Urban heat islands (UHIs) represent a significant manifestation of climate change impacting cities globally. In African coastal cities, often situated in low-lying areas with stagnant air, rapid demographic growth, and irreversible land-use changes, the proliferation of heat islands poses considerable risks to vulnerable urban populations. Notable cities experiencing this phenomenon include Lagos (Nigeria), Cairo (Egypt), Johannesburg (South Africa), Nairobi (Kenya), and Dakar (Senegal). This study investigates the interplay between land-use changes, the emergence of heat islands, and the vulnerability of residents in the seaside and port city of Kribi, Cameroon. Furthermore, it explores effective adaptation strategies to mitigate the impacts of heat islands. Google Earth (GE) imagery from 2015, 2019, and 2023 is utilized to assess land-use dynamics. Surface temperatures are analyzed for 2015, 2017, 2019, and 2023 using Landsat 8 and 9 imagery processed with QGIS 2.18 software. Meteoblue meteorological data are employed to validate the findings. A GPS survey of air conditioners in Kribi, conducted using the SWMap mobile application, provides insights into stakeholder involvement and the categories of air conditioning units. Additionally, a questionnaire administered to 200 city dwellers gathers information on their vulnerability to heat islands and their mitigation strategies. It also carries out a prospective analysis of the evolution of urban heat islands in the city of Kribi using linear regression and statistical modeling approaches. Currently, surface temperatures in Kribi are estimated to range from 26Â°C to 35Â°C between 2015 and 2023, with notable spatial variations in heat islands. The projection to 2033 (10 years) shows that heat islands will intensify, although temperature values will remain more or less the same. To cope with these rising temperatures, most building occupants rely on air conditioning. Over 41% of surveyed residents use air conditioning in their homes, with the highest proportion found in hotel and catering facilities (52%), followed by service offices (16%) and private residences (14%). Green space in Kribi has drastically declined from 2015 to 2023. In 2015, green space accounted for 5,169 ha (83%), but by 2023, it had shrunk to 2,516 ha (43%), resulting in a loss of 2,653 ha. This decline was evident between 2015 and 2019, with green space decreasing from 4,908 ha (83%) to 2,516 ha (43%). The study underscores the importance of integrated management of urbanization and natural resources to address the challenges posed by climate change and rapid urbanization. It also discusses the implications for other African countries. This approach will not only aid in identifying solutions tailored to Kribi but will also generate more general recommendations applicable to other cities facing similar challenges related to urbanization and climate change.